Technology Entrepreneurship Project (ENT 600) : Decathlon Group / Muhammad Akmal Mohd Shobri - Mohd Shobri, Muhammad Akmal (2021)
This is an endeavor to grasp how the theories can be applied to a practical situation. As a student in UiTM Perlis, it is a part of a study for everyone to undergo a case study project. So, for this purpose, I got the chance to research a corporate entity that manufactures a product that deeply interests us, which is Decathlon Group, a sports retailer. First of all, the general information regarding the corporate has been collected. Information is gathered through the primary and secondary source. In the second part of the report contains the specialized subject studies. The objective of the project is to figure on the background, organizational structure, products and services that Decathlon provides. In this case study, I have analyzed the strength, weaknesses, opportunities, and threats of this company in the real business world by using SWOT analysis. Next, I studied regarding the product manufactured by Decathlon, which is primarily a standard technology utilized by the company for its selected product that we have chosen which is their running shoes. Here, I will be explaining the problems of the shoes that have grab my attention. The problem of the shoes that I discovered is the shoes are instable which makes difficulties for runners. Next, is the shoe has a high arch which is not suitable for runners. And lastly, the narrowed shoes developed by Decathlon has made it difficult for those who have wide feet to wear it. In this study, I will be explaining deeper regarding the problems and I would also be discussing the alternatives solutions towards the problems.